Comparative Analysis of Flavonoid and Phenolic Contents and Antioxidant Capacity in Different Plant Parts of Artemisia - Yefrida Yefrida; Y.T. Putri; R Refilda (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Free radicals can lead to oxidative stress, causing cell damage, which underlines the importance of natural antioxidants. Although the genus Artemisia (Asteraceae) is a widely recognized source of bioactive compounds, comparative data on its antioxidant potential in specific organs remain scarce. In this study, the total flavonoid content (TFC), total phenolic content (TPC), and antioxidant capacity of the leaves, stems, and roots of four Artemisia species were evaluated, as well as their relationships. Total phenolic and flavonoid contents, determined by Folin–Ciocalteu and AlCl? methods respectively. The antioxidant capacity was determined using the DPPH test. The distribution patterns of phytochemicals and antioxidant capacity across organs were heterogeneous. Leaves contained the highest content of flavonoids and phenolic compounds, while roots demonstrated the strongest antioxidant capacity except for Artemisia vulgaris. Results show that plant components and species varied significantly (ANOVA, p < 0.05). The flavonoid and phenolic content of stems and leaves were strongly positively correlated with antioxidant capacity, while phenolic and flavonoid levels throughout the plant were closely correlated. These findings provide novel comparative insights into the antioxidant properties of flavonoid and phenolic compounds across different tissue types of diverse Artemisia species, as well as aiding the rational selection of plant material for potential applications in natural antioxidant use. Contribution to Sustainable Development Goals (SDGs):SDG 3 : Good Health and Well-BeingSDG 12 : Responsible Consumption and ProductionSDG 15 : Life on Land